RESULTS OF COMPLEX INVESTIGATIONS OF POPULATION REPRODUCTION PROCESSES IN LOCAL GROUPS OF TOBOL-IRTYSH SIBERIAN TATARS IN TYUMEN REGION: GENETIC AND DEMOGRAPHIC ASPECTS - M. V. Ulyanova; M. B. Lavryashina; V. V. Poddubikov; M. R. Zazulina; K. I. Osipov; A. P. Chemchieva; Z. A. Tychinskih; B. A. Tkhorenko; A. M. Vedenin; O. N. Nechiporenko; V. G. Druzhinin (Вестник Кемеровского государственного университета, 2015)
The paper discusses the results of a study of the dynamics (1940 – 2014) of the genetic and demographic process in local populations Tobol-Irtysh Siberian Tatars inTyumenregion. The Tatars of Tyumen-Turin, Tobolsk and Yaskolbinsk groups were examined. A unidirectional dynamics of the genetic and demographic processes and indicators of reproduction was discovered: aging of the rural population, decline in the proportion of the reproductive group of the population, imbalance in the sex structure with men prevailing over of women in the reproductive group of the population, increasing rates of inter-ethnic mixing, rising levels of migration activity. Different intensity of these processes in the different studied groups of local population was identified.